2012
DOI: 10.1109/led.2012.2194130
|View full text |Cite
|
Sign up to set email alerts
|

Scaled Self-Aligned N-Polar GaN/AlGaN MIS-HEMTs With $f_{T}$ of 275 GHz

Abstract: In this letter, we demonstrate state-of-the-art performance from N-polar GaN/AlGaN metal-insulator-semiconductor high-electron-mobility transistors. Self-aligned gate-first process was used for the fabrication of transistors. Graded InGaN and InN contact layers were used to achieve low ohmic contact resistance. The GaN channel thickness was scaled to 7 nm from previous generation of N-polar GaN devices to improve the aspect ratio and hence achieve better small-signal performance. The devices reported f T of 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…Even when L G scales down to 30 nm for an optimized gate geometry, the extra gate fringing capacitance induced by the dielectrics surrounding the gate is still not the major factor impacting the device performance. It has been reported that the f T for the devices with a relatively high-κ SiN x or SiON layer surrounding the gate was only ∼23% lower than that of the devices with the gate surrounding dielectrics removed [5], [8]. One can expect that carefully optimizing the gate geometry and using low-κ dielectrics under the gate head can further reduce the parasitic gate fringing capacitance.…”
Section: A DC and Rf Characteristics At Rtmentioning
confidence: 99%
See 2 more Smart Citations
“…Even when L G scales down to 30 nm for an optimized gate geometry, the extra gate fringing capacitance induced by the dielectrics surrounding the gate is still not the major factor impacting the device performance. It has been reported that the f T for the devices with a relatively high-κ SiN x or SiON layer surrounding the gate was only ∼23% lower than that of the devices with the gate surrounding dielectrics removed [5], [8]. One can expect that carefully optimizing the gate geometry and using low-κ dielectrics under the gate head can further reduce the parasitic gate fringing capacitance.…”
Section: A DC and Rf Characteristics At Rtmentioning
confidence: 99%
“…ohmic contact regrowth [2]- [9], [12], [13], advanced T -gate fabrication process [2]- [6], [9], or a gate-first self-aligned approach [4], [8]. f T and f max of GaN HEMTs can be primarily improved through the downscaling of device geometry, whereas the aspect ratio (gate length and gate-to-channel distance) has to be maintained for the mitigation of short-channel effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of epitaxial growth and processing techniques, both excellent highfrequency and RF power performance have been achieved in N-polar GaN/AlGaN HEMTs. [4][5][6] Specifically, the gate length (L g ) of GaN HEMTs has been aggressively scaled down to improve the high frequency performance of transistors. However, various non-idealities including short-channel effects have restricted the performance of ultra-scaled GaN HEMTs.…”
mentioning
confidence: 99%
“…[http://dx.doi.org/10.1063/1.4799286] AlGaN/GaN heterostructure-based high electron mobility transistors have attracted considerable attention for their excellent performance in high-frequency and high-power applications. [1][2][3][4] However, heteroepitaxial AlGaN layers grown on GaN substrates are subjected to significant mechanical stresses because of the large lattice mismatch between AlN and GaN. The existence of biaxial stress results in the appearance of in-plane strain.…”
mentioning
confidence: 99%